Developmental Changes in Locating Voice and Sound in Space - Kezuka, Emiko; Amano, Sachiko; Reddy, Vasudevi (Frontiers in Psychology, 2017)
We know little about how infants locate voice and sound in a complex multi-modal space. Using a naturalistic laboratory experiment the present study tested 35 infants at 3 ages: 4 months (15 infants), 5 months (12 infants) and 7 months (8 infants). While they were engaged frontally with one experimenter, infants were presented with a) a second experimenter’s voice and b) castanet sounds from three different locations (left, right, and behind). There were clear increases with age in the successful localization of sounds from all directions, and a decrease in the number of repetitions required for success. Nonetheless even at 4 months two-thirds of the infants attempted to search for the voice or sound. At all ages localizing sounds from behind was more difficult and was clearly present only at 7 months. Perseverative errors (looking at the last location) were present at all ages and appeared to be task specific (only present in the 7 month-olds for the behind location). Spontaneous attention shifts by the infants between the two experimenters, evident at 7 months, suggest early evidence for infant initiation of triadic attentional engagements. There was no advantage found for voice over castanet sounds in this study. Auditory localization is a complex and contextual process emerging gradually in the first half of the first year.